Fabry-Pérot Interferometer : construction, calibration and developement - Khan, Hasan (2015)
The work presented in this thesis concentrates on the construction and development of a Fabry-Perot Interferometer (FPI). Resonance ionization spectroscopy (RIS) is a powerful technique for the extraction of nuclear structure, namely nuclear spins, moments and changes in mean-square charge radii. However, due to the pulsed nature of the laser, the technique may be limited by the laser linewidth to low resolution spectroscopy. This thesis presents the construction and characterization of a Fabry-Perot Interferometer in order to measure the laser linewidth and to calibrate the wavelength of a pulsed Ti:Sapphire laser in "Narrowband" mode (<1 GHz). The FPI has been directly utilized in the measurements of optical transitions via resonance ionization spectroscopy of copper.